Zrównoważony rozwój w technologii chemicznej na świecie - Bogoczek, Romuald (Sustainable development of engineering chemistry in the world, 2007)
In this paper, the Chemical technology has been described as a domain of human activity which is essential to sustain the current level of civilization for an unusually high number of population on earth. The negative influence of Chemical technology on the environment as well as on the health of the community at large was also described. Green Chemistry has been shown as an antidote to that dichotomy. Green Chemistry is the technological version of the sustainable development of human society. It has been shown that in the Wrocław University of Economics both the technological and the economic directions of the sustainable development are being developed and two of international conferences have been held on the technological methods and means which diminish the Chemical and technological environmental impact. It has been shown how technology should develop to not threaten the environment. At the end of the paper, a review of the most valuable articles on Green Chemistry was given what should give the reader a possibility familiarized with the rangę of involvement by engineers and Polish scientists and chemists in launching new ways of sustainable development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 211-223